Interactions between maternal parity and feed additives drive the composition of pig gut microbiomes in the post-weaning period - Kayla Law; Eduardo Rosa Medina Garcia; Chad Hastad; Deborah Murray; Pedro E. Urriola; Andres Gomez (Journal of Animal Science and Biotechnology, 2024)
Abstract Background Nursery pigs undergo stressors in the post-weaning period that result in production and welfare challenges. These challenges disproportionately impact the offspring of primiparous sows compared to those of multiparous counterparts. Little is known regarding potential interactions between parity and feed additives in the post-weaning period and their effects on nursery pig microbiomes. Therefore, the objective of this study was to investigate the effects of maternal parity on sow and offspring microbiomes and the influence of sow parity on pig fecal microbiome and performance in response to a prebiotic post-weaning. At weaning, piglets were allotted into three treatment groups: a standard nursery diet including pharmacological doses of Zn and Cu (Con), a group fed a commercial prebiotic only (Preb) based on an Aspergillus oryzae fermentation extract, and a group fed the same prebiotic plus Zn and Cu (Preb + ZnCu). Results Although there were no differences in vaginal microbiome composition between primiparous and multiparous sows, fecal microbiome composition was different (R 2 = 0.02, P = 0.03). The fecal microbiomes of primiparous offspring displayed significantly higher bacterial diversity compared to multiparous offspring at d 0 and d 21 postweaning (P < 0.01), with differences in community composition observed at d 21 (R 2 = 0.03, P = 0.04). When analyzing the effects of maternal parity within each treatment, only the Preb diet triggered significant microbiome distinctions between primiparous and multiparous offspring (d 21: R 2 = 0.13, P = 0.01; d 42: R 2 = 0.19, P = 0.001). Compositional differences in pig fecal microbiomes between treatments were observed only at d 21 (R 2 = 0.12, P = 0.001). Pigs in the Con group gained significantly more weight throughout the nursery period when compared to those in the Preb + ZnCu group. Conclusions Nursery pig gut microbiome composition was influenced by supplementation with an Aspergillus oryzae fermentation extract, with varying effects on performance when combined with pharmacological levels of Zn and Cu or for offspring of different maternal parity groups. These results indicate that the development of nursery pig gut microbiomes is shaped by maternal parity and potential interactions with the effects of dietary feed additives.